Processing fluency hinders subsequent recollection: an electrophysiological study - Li, Bingbing; Gao, Chuanji; Wang, Wei; Guo, Chunyan (Frontiers in Psychology, 2015)
Although many behavioural studies have investigated the effect of processing fluency on subsequent recognition memory, little research has examined the neural mechanism of this phenomenon. The present study aimed to explore the electrophysiological correlates of the effects of processing fluency on subsequent recognition memory by using an event-related potential (ERP) approach. The masked repetition priming paradigm was used to manipulate processing fluency in the study phase, and the R/K paradigm was utilised to investigate which recognition memory process (familiarity or recollection) was affected by processing fluency in the test phase. Converging behavioural and ERP results indicated that increased processing fluency impaired subsequent recollection. Results from the analysis of ERP priming effects in the study phase indicated that increased perceptual processing fluency of object features, reflected by the N/P 190 priming effect, can hinder encoding activities, reflected by the LPC priming effect, which leads to worse subsequent recollection based recognition memory. These results support the idea that processing fluency can influence subsequent recognition memory and provide a potential neural mechanism underlying this effect. However, further studies are needed to examine whether processing fluency can affect subsequent familiarity.